Promotion of Internet Users’ Aggressive Participation via the Mediators of Flow Experience and Identification - Chang, Kuei-Feng; Huang, Yu-Huang; Li, Wei-Chin; Luo, Shunjun; Yang, Dong-Jenn (Frontiers in Psychology, 2022)
Social media users have increased rapidly in recent years; however, most are “silent users” who rarely share information online. To maintain the stable operation and development of social media companies, this research explored the effects of flow experience and identity formation on users’ intrinsic motivation to facilitate aggressive, spontaneous, and habitual participation in virtual communities. A total of 487 valid questionnaires were collected and underwent regression analysis. The results revealed that all three intrinsic motivations had significant impacts on social media participation, with social interaction exerting the strongest influence. Flow experience and identification had significant, partial mediating effects on the relationship between motivation and participation. Based on the results, several suggestions were provided to help social media enterprises increase user participation. It is hoped that this research could facilitate in transforming users into habitual participants to keep the operations of the virtual community stable and enduring.